Proses Bleach Washing pada Kain Denim yang Dicelup dengan Zat Warna Indigo Menggunakan Natrium Hipochlorit (NaOCl) - Luciana Luciana; Elly Koesneliwati (Sainteks: Jurnal Sain dan Teknik, 2021)
The process of bleach washing on denim fabrics produces a paler or lighter shabby effect. The shabby effect is produced by using an oxidizing agent. The application of sodium hypochlorite can cause a decrease in color aging of denim fabrics and high tensile strength. The pH condition also affects the occurrence of oxycellulose damage which will affect the final result. Inappropriate pH will cause a very high oxidation process and produce a less shabby effect and can cause a decrease in tensile strength. Therefore, the concentration of NaOCl and pH must be adjusted properly so that optimal results are obtained. The purpose of this study was to determine the effect of optimum concentration of sodium hypochorite (NaOCl) and pH on the physical properties of denim fabric. After the process of bleach washing process experiment was carried out, a test was carried out based on two-factor Anova statistical data and the optimum visual test fabric results were obtained at a NaOCl concentration of 2 g/L using alkaline pH (10-11). The test values were obtained as follows: color fastness to rubbing are 3-4 for dry, 2-3 for wet, tensile strength 67.4 kg in warp direction, 43.1 in weft direction, fabric stiffness in warp direction 430.48, weft direction 344.54. The factory standard for a tensile strength of 65 kg warp direction, 40 kg weft direction, color fastness to rubbing 3 for dry rubbing and 2 for wet rubbing. Keywords: bleach washing, denim, sodium hypochlorite, oxycellulose, color fastnes